2021
DOI: 10.1021/acs.jafc.1c05830
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intestinal Barriers by Puerarin in Combination with Tryptophan

Abstract: The intestinal barrier is essential for maintaining human intestinal health. The growing number of studies has shown that both puerarin and tryptophan and its metabolites have a beneficial effect on the intestinal barrier. This study aims at the combination of puerarin and tryptophan or its metabolites for improving the intestinal barrier. In our study, 40 female Sprague− Dawley rats were randomly divided into five groups (n = 8) for a 4-week experiment and dextran sodium sulfate was used to induce an intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Indole strengthened epithelial cell barrier properties by increasing tight junction resistance, and attenuated indicators of inflammation ( 6 ). Indole-3-propionic acid decreased FITC-dextran-dependent gut permeability in mice ( 22 24 ), increased mucin secretion in human colonic cells ( 9 ), increased goblet cell numbers and mucosa thickness in rats ( 25 ), and acted as a ligand of the aryl hydrocarbon receptor (AhR) and exerted an anti-inflammatory effect in colon ( 26 ). In this study, dietary ICA supplementation in weaned piglets did not alter intestinal morphological characteristics including the villus height, crypt depth, and villus height/crypt depth ratio, and had no influence on intestinal permeability as reflected by DAO, D-lactic acid and endotoxin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Indole strengthened epithelial cell barrier properties by increasing tight junction resistance, and attenuated indicators of inflammation ( 6 ). Indole-3-propionic acid decreased FITC-dextran-dependent gut permeability in mice ( 22 24 ), increased mucin secretion in human colonic cells ( 9 ), increased goblet cell numbers and mucosa thickness in rats ( 25 ), and acted as a ligand of the aryl hydrocarbon receptor (AhR) and exerted an anti-inflammatory effect in colon ( 26 ). In this study, dietary ICA supplementation in weaned piglets did not alter intestinal morphological characteristics including the villus height, crypt depth, and villus height/crypt depth ratio, and had no influence on intestinal permeability as reflected by DAO, D-lactic acid and endotoxin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the GBB demonstrate that indole [10] and IPA [20,116,117], two tryptophan metabolites, improve barrier properties by increasing the expression of claudins and other tight junction proteins. Additionally, IPA increases secretion of mucins in in vitro human colonic culture [20] and increases the number of goblet cells and mucosa thickness in rats [118]. Moreover, IPA acts as a ligand of the aryl hydrocarbon receptor (AhR) present in colonic epithelial cells, activation of which is associated with anti-inflammatory and anticancer effects [119] Interestingly, it has been observed that in patients suffering from colitis serum, IPA concentration decreases significantly [28].…”
Section: Ipa Improves Gut-blood Barrier Functionmentioning
confidence: 99%
“…1 The destruction of the intestinal mucosal barrier increases intestinal permeability, which leads to harmful substances passing through intestinal epithelial cells and entering circulation, mediating the chronic inflammatory state of the whole body, 2 including inflammatory bowel disease, alcoholic and nonalcoholic liver diseases, and food allergies. 3,4 Therefore, the integrity of the intestinal barrier plays an important role in the physiological regulation of human beings. 5 To date, research on the intestinal barrier has been a hot topic in food science and clinical medicine.…”
Section: Introductionmentioning
confidence: 99%